The lovelorn ghost and the magical monk : practicing Buddhism in modern Thailand - McDaniel, Justin (Columbia University Press, 2011)
"Focusing on representations of the ghost and monk from the late eighteenth century to the present, Justin Thomas McDaniel builds a case for interpreting modern Thai Buddhist practice through the movements of these transformative figures ... Listening to popular Thai Buddhist ghost stories, visiting crowded shrines and temples, he finds concepts of attachment, love, wealth, beauty, entertainment, graciousness, security, and nationalism all spring from engagement with the ghost and the monk and are as vital to the making of Thai Buddhism as venerating the Buddha himself."--Jacket.